Development of a Ferrite-Based Electromagnetic Wave Detector - Muhammad Hanish Zakariah; Poppy Puspitasari; Nur Aliza Ahmad (Universitas Negeri Malang, 2017)
Direct detection of hydrocarbon by an active source using electromagnetic (EM) wave termed Sea Bed Logging (SBL) has shown very promising results. However, currently available electromagnetic wave technology has a number of challenges including sensitivity and lapsed time. Our initial response to this issue is to develop a ferrite-based EM wave detector for Sea Bed Logging (SBL). Ferrite bar and copper rings in various diameters were used as detector 1 (D1). For Detector 2 (D2), toroid added with copper wires in different lengths at the centre of it were used. The first experiment is to determine the inductance and resistance for both detectors by using LCR meter. We obtained the highest inductance value of 0.02530 mH at the ferrite bar when it was paired with a 15 cm diameter copper ring and 0.00526 mH for D2 using a 100 cm copper wire placed at the centre of the toroid. The highest resistivity for D1 was measured at ferrite bar paired with a 15 cm diameter copper ring and 1.099 Ω when using 20 cm length of copper wire. The second interest deals with voltage peak-to-peak (Vp-p) value for both detectors by using oscilloscope. The highest voltage value at the ferrite bar of D1 was 25.30 mV. While at D2, the highest voltage measured was 27.70 mV when using a 100 cm copper wire. The third premise is the comparison of sensitivity and lapsed time for both detectors. It was found that D1 was 61% more sensitive than D2 but had higher lapsed time than D2.